Une relecture de l’événement : La chute du Royaume arabe de Damas en 1920 - Jean-David Mizrahi (Revue des Mondes Musulmans et de la Méditerranée)
The purpose of this article is to provide an interpretation of that event by grasping, on the contrary, the meaning of the framework at stake “in the long term”. Therefore, we have, first and foremost, sought to understand the transformations of the Syrian political arena in those days in the light of economic and social changes that affected the Bilâd al-Shâm during a long Ottoman 19th century, before exploring the intellectual history and that of representations, and being aware that the civilizing example of the Arabian kingdom, inherited from the Europe of the Enlightenment, was eventually bound to come up against a radical and populist trend in the Arab nationalism.